Molecular docking study of xylogranatins binding to glycogen synthase kinase-3β - Christian Bailly; Gérard Vergoten (KeAi Communications Co., Ltd., 2022)
Objective: The mangrove tree Xylocarpus granatum J. Koenig (X. granatum) is a medicinal plant used to treat various diseases in several Asian countries. Many bioactive natural products have been isolated from the plants, particularly several groups of limonoids, including 18 xylogranatins (Xyl-A to R), all of which bear a furyl-δ-lactone core commonly found in limonoids. Based on a structural analogy with the limonoids obacunone and gedunin, we hypothesized that xylogranatins could target the enzyme glycogen synthase kinase-3β (GSK-3β), a major target for the treatment of neurodegenerative pathologies, viral infections, and cancers. Methods: We investigated the binding of the 18 xylogranatins to GSK-3β using molecular docking in comparison with two known reference GSK-3β ATP-competitive inhibitors, LY2090314 and AR-A014418. For each compound bound to GSK-3β, the empirical energy of interaction (ΔE) was calculated and compared to that obtained with known GSK-3β inhibitors and limonoid triterpenes that target this enzyme. Results: Five compounds were identified as potential GSK-3β binders, Xyl-A, -C, -J, -N, and -O, for which the calculated empirical ΔE was equivalent to that calculated using the best reference molecule AR-A014418. The best ligand is Xyl-C, which is known to have marked anticancer properties. Binding of Xyl-C to the ATP-binding pocket of GSK-3β positions the furyl-δ-lactone unit deep into the binding-site cavity. Other xylogranatin derivatives bearing a central pyridine ring or a compact polycyclic structure are much less adapted for GSK-3β binding. Structure-binding relationships are discussed. Conclusion: GSK-3β may contribute to the anticancer effects of X. granatum extract. This study paves the way for the identification of other furyl-δ-lactone-containing limonoids as GSK-3β modulators.